THE EFFECT OF USING PICTURES SERIES ON STUDENTS’ WRITING PARAGRAPH AT SMAN 2 LAKUDO - Mido, La; Irjayanti Herman, Ary (English Education Journal, 2025)
The problem statement, “was there any significant differences effect on writing paragraph between group of students were taught by using pictures series and group on students who were taught with non using pictures series. The objective of this study was to find out if there was a significant differences effect on writing paragraph between group of students were taught by using pictures series and group on students who were taught with non using pictures series.” The present research employed a non-equivalent control group design and was classified as a quasi-experimental design. The population of this research consisted of all second-grade students at SMAN 2 Lakudo, which is a senior high school with six classes and a total of 150 students. The sample for this study consisted of approximately two classes, each of which had twenty-five students, selected using the cluster random sampling technique. The objective assessment used in the present study was a paragraph-writing activity. The SPSS 13 program was employed to collect data through pretests, posttests, and analysis. The findings of this study indicated that the use of picture series has a significant differential impact on students' paragraph writing when comparing those who taught by using picture series to those who taught without using pictures series. In this study, the experimental class (which received treatment using pictures) demonstrated greater comprehension of the text in comparison to the control class. This is evident in the mean score and the results of the ANOVA Analysis.